Daily Functionality in Adults with POTS: Predictive Factors. Issue 3 (1st July 2022) - Vas, Asha; Rich, Emily; Wang, Wanyi; Patterson, Meaghan; Parsons, Thomas
Abstract: Symptoms associated with postural orthostatic tachycardia syndrome (POTS) hinder overall functionality. This study examined factors that impacted daily life and contributed to overall daily functionality in adults with POTS ( n  = 958, ages 18–60). Descriptive and multiple linear regression analyses indicated that participants with fewer challenges in ADLs, IADLs, work, school, leisure, and socializing had overall better functionality. Furthermore, 'younger age with exercise tolerance', 'having a job', and 'no falls in the last year' were predictors of better functionality. A comprehensive approach to addressing physical, environmental, and psychological factors could help improve overall functionality and enhance quality of life in individuals with POTS.